A Study on Indian Consumers' Attitude and Choice of Preferences for Green Attributes of the Hotel Industry - Kasliwal, Neeti; Agarwal, Srishti (Prabandhan: Indian Journal of Management, 2015)
Hotels are the most important part of the tourism industry, which contribute to the sector by offering services and facilities of extremely high standards. Today, the hospitality industry is becoming more aware about the environment-friendly services. However, whether Indian consumers are aware about the green attributes offered by the hotel industry needed to be analyzed. The present study examined the Indian consumers' awareness, perceptions, and choice of preferences for the green attributes of the hotel industry. Data was collected using a structured questionnaire distributed to 300 respondents in Jaipur city, Rajasthan. The results obtained by using tests like chi square, percentage mean method, and one sample t - test showed that there is a significant association between awareness, perception, and choice of preferences for the green attributes of the hotel industry. Based on the results, the findings and implications are also discussed in the paper.